2020
DOI: 10.1017/s2045796020000517
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent explosive disorder subtypes in the general population: association with comorbidity, impairment and suicidality

Abstract: Aims Intermittent explosive disorder (IED) is characterised by impulsive anger attacks that vary greatly across individuals in severity and consequence. Understanding IED subtypes has been limited by lack of large, general population datasets including assessment of IED. Using the 17-country World Mental Health surveys dataset, this study examined whether behavioural subtypes of IED are associated with differing patterns of comorbidity, suicidality and functional impairment. Methods IED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Data from the World Mental Health Survey (Scott et al, 2020) indicate that the lifetime prevalence of intermittent explosive disorder in 17 countries was 0.8%. Data from U.S. studies have shown a higher prevalence (Coccaro, 2012).…”
Section: Intermittent Explosive Disorder Presentations and Symptom Pa...mentioning
confidence: 99%
“…Data from the World Mental Health Survey (Scott et al, 2020) indicate that the lifetime prevalence of intermittent explosive disorder in 17 countries was 0.8%. Data from U.S. studies have shown a higher prevalence (Coccaro, 2012).…”
Section: Intermittent Explosive Disorder Presentations and Symptom Pa...mentioning
confidence: 99%